Modelling Agricultural Policies in the CEE Accession Countries - d'Artis Kancs; Gerald Weber (Economics and Econometrics Research Institute (EERI), 2001)
The present paper analyses sectoral impacts of the CEE integration with EU. Adopting a par-tial equilibrium model we explicitly model the agricultural sector in CEE. The underlying par-tial equilibrium model is based on the duality theory. The model captures all key CAP instru-ments, such as price support, area payments, animal premiums, quotas and set-aside premiums. The policy simulation analysis allows us to track how changes in the CAP affect the supply and demand behaviour of agricultural producers and consumers of food products. Our simulation results suggest that farm income in CEE will rise mainly due to area payments and animal pre-miums. The impact on consumer welfare is rather small, as decreasing prices for some food products are offset by increasing prices for other agricultural goods.
Keywords: D13; J20; J23; P36; Q12; 330; Policy modelling; partial equilibrium model; CEE; CAP